2010
DOI: 10.1038/emboj.2010.43
|View full text |Cite
|
Sign up to set email alerts
|

AIF promotes chromatinolysis and caspase-independent programmed necrosis by interacting with histone H2AX

Abstract: Programmed necrosis induced by DNA alkylating agents, such as MNNG, is a caspase-independent mode of cell death mediated by apoptosis-inducing factor (AIF). After poly(ADP-ribose) polymerase 1, calpain, and Bax activation, AIF moves from the mitochondria to the nucleus where it induces chromatinolysis and cell death. The mechanisms underlying the nuclear action of AIF are, however, largely unknown. We show here that, through its C-terminal proline-rich binding domain (PBD, residues 543-559), AIF associates in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
225
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 197 publications
(233 citation statements)
references
References 65 publications
7
225
1
Order By: Relevance
“…This approach showed that MNNG Figure 2D). Overtime, similarly to what has been previously reported for MNNG-treated H2AX À/À MEFs, 14 it seems that the cell is unable to achieve the necroptotic PCD program in the absence of BID. As a result, the 'highly damaged' cell, which is unable to proliferate/divide (Supplementary Figure 3), explodes by an uncontrolled form of necrosis.…”
Section: Resultssupporting
confidence: 51%
See 4 more Smart Citations
“…This approach showed that MNNG Figure 2D). Overtime, similarly to what has been previously reported for MNNG-treated H2AX À/À MEFs, 14 it seems that the cell is unable to achieve the necroptotic PCD program in the absence of BID. As a result, the 'highly damaged' cell, which is unable to proliferate/divide (Supplementary Figure 3), explodes by an uncontrolled form of necrosis.…”
Section: Resultssupporting
confidence: 51%
“…8 Once in mitochondria, BAX provokes a mitochondrial damage that is accompanied by the release of tAIF, the truncated form of AIF, to the cytosol and nucleus (Figures 1d and e). 8,14 In the nucleus, this apoptogenic protein generates TUNELdetectable 3 0 -OH DNA breaks in DNA (Figure 1f). Altogether, these events represent the biochemical hallmarks of MNNG-mediated necroptosis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations